(untitled) (The Informal: South Asian Journal of Human Rights and Social Justice, 2025)
Nepal’s transitional justice process, initiated after the 2006 Comprehensive Peace Accord, has been repeatedly hindered by political interference, legal ambiguity, and institutional inertia. Despite multiple cycles of the Truth and Reconciliation Commission (TRC) and the Commission of Investigation on Enforced Disappeared Persons (CIEDP), the experiences of women—particularly victims of conflict-related sexual violence (CRSV), widows, and female ex combatants—remain systematically excluded. This paper examines the gendered and intersectional failures of Nepal’s transitional justice framework through a feminist lens. It critiques the state’s reliance on patriarchal evidentiary norms, token participation, and structural silence, especially in how sexual violence, enforced disappearance, and reintegration are addressed. Drawing on victim testimonies, legal rulings, UN recommendations, and provincial consultations held in 2025, this paper argues that Nepal’s transitional justice must be fundamentally remained as a victim-centered, gender-responsive process. It concludes by offering concrete legal and institutional reforms to advance an inclusive and transformative model of justice.